2022
DOI: 10.3390/biomedicines10051005
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Depression: Chronic Stress Alters the Glutamatergic System in the Brain—Focusing on AMPA Receptor

Abstract: Major depressive disorder (MDD) is a common neuropsychiatric disorder affecting the mood and mental well-being. Its pathophysiology remains elusive due to the complexity and heterogeneity of this disorder that affects millions of individuals worldwide. Chronic stress is frequently cited as the one of the risk factors for MDD. To date, the conventional monoaminergic theory (serotonin, norepinephrine, and/or dopamine dysregulation) has received the most attention in the treatment of MDD, and all available classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 115 publications
1
11
0
Order By: Relevance
“…The hippocampal neurons investigated by Moravcikova and colleagues were presumably pyramidal glutamatergic ones, as it was assumed from their morphology and characteristic ion currents across the membrane. Since hippocampal glutamate transmission is involved in antidepressant drugs response (Hlavacova et al 2018;Lee et al 2022), it is possible that anxiolytic and antidepressant-like effects of SNC80, observed in previous studies, are explained, at least in part, via the ability of this ligand to modulate the firing activity of hippocampal neurons. To test this hypothesis, the effect of SNC80, as well as of the selective DOR antagonist naltrindole, on the excitability of hippocampal glutamate neurons, should be tested in in vivo conditions.…”
Section: Introductionmentioning
confidence: 98%
“…The hippocampal neurons investigated by Moravcikova and colleagues were presumably pyramidal glutamatergic ones, as it was assumed from their morphology and characteristic ion currents across the membrane. Since hippocampal glutamate transmission is involved in antidepressant drugs response (Hlavacova et al 2018;Lee et al 2022), it is possible that anxiolytic and antidepressant-like effects of SNC80, observed in previous studies, are explained, at least in part, via the ability of this ligand to modulate the firing activity of hippocampal neurons. To test this hypothesis, the effect of SNC80, as well as of the selective DOR antagonist naltrindole, on the excitability of hippocampal glutamate neurons, should be tested in in vivo conditions.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that depressive-like states disrupt excitatory synaptic transmission and synaptic plasticity [ 107 ]. Synaptic transmission and plasticity are tightly regulated by serotonergic signaling [ 108 ], which is related to important physiological processes, such as sleep, body temperature, appetite, pain and motor activity [ 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting increased levels of glutamate in the prefrontal cortex of individuals who have committed suicide, suggesting dysregulation in glutamate and GABA excitation/inhibition signalling. Subsequently a glutamatergic theory has been formulated to explain the development of depression [ 14 , [10] , [15] , [16] ]. The neuroinflammatory theory proposes chronic exposure to inflammatory mediators to trigger the development of depression, where inflammation is believed to drive many of the neurodegenerative processes observed in depression [ [17] , [18] , [19] ].…”
Section: Pathogenesis Of Mddmentioning
confidence: 99%